P113 The Use Of Local Anaesthesia In Improving The Patient Experience Of Arterial Blood Gases: Students And Trainers Are Still Not Getting The Message. (10th November 2014) - Mangera, Z; Gunasekera, C; Kinley, J; King, J; Walker, B; Cohen, O; Dilworth, P
Abstract : Background: BTS guidelines (2008) states that "local anaesthesia (LA) should be used for all arterial blood gas (ABG) specimens except in emergencies 1 as it improves the patient experience. A survey conducted in 2012 revealed only 5% of junior doctors regularly use LA with ABGs. 2 We were interested to determine if this has improved and establish whether medical students are being orientated to this practice. Methodology: This is a multicentre prospective study. A questionnaire survey was distributed to 4th year medical students and junior doctors affiliated with UCL Medical School. Questions related to their actual experiences of using LA with ABGs and barriers to using LA. Results: 94 medical students completed the questionnaire. Students used LA 17% of the time out of 54 supervised procedures. 29% were actively discouraged from using LA by their supervising doctor. 10% felt the general culture amongst supervising doctors was resistant to using LA. Amongst the 86 surveyed doctors, 91% never or rarely (<10% of the time) used LA, 5% sometimes (<25% of the time) and 3% used it regularly (>75% of the time). 65% of doctors were not aware that LA was advised in national guidance. 40% of respondents felt it would not reduce the pain of the procedure and 38% did not know the technique involved of using LA. Conclusion: The use of LA is extremely poor as has been found previously. 1 The reasons reflect a lack of awareness and a culture that is experienced from the moment the enter the clinical environment as medical students. In order to improve the patient experience we have introduced an intervention at the level of the medical school and junior doctor teaching which includes mandatory training and encouraging affiliated trusts to help create a culture where giving LA is the norm. We will fully report on the results and success of our interventions. References: O'Driscoll, Howard LS, Davison AG. BTS guideline for emergency oxygen use in adult patients. Thorax . 2008; 63 (Suppl VI):vi1–vi73 Khan F et al . The Use of Local Anaesthesia For Arterial Blood Gas Sampling – A Multicentre Survey. Thorax 2012;67:A167-A168